The People want the Fall of the Regime: Schooling, Political Protest, and the Economy - CAMPANTE, Filipe R. (Institutional Knowledge at Singapore Management University, 2011)
We provide evidence that economic circumstances are a key intermediating variable for understanding the relationship between schooling and political protest. Using the World Values Survey, we find that individuals with higher levels of schooling, but whose income outcomes fall short of that predicted by their biographical characteristics, in turn display a greater propensity to engage in protest activities. We discuss a number of interpretations that are consistent with this finding, including the idea that economic conditions can affect how individuals trade off the use of their human capital between production and political activities. Our results could also reflect a link between education, ‘‘grievance’’, and political protest, although we argue that this is unlikely to be the sole explanation. Separately, we show that the interaction between schooling and economic conditions matters too at the country level: Rising education levels coupled with macroeconomic weakness are associated with increased incumbent turnover, as well as subsequent pressures toward democratization.